PENGARUH PERHUTANAN SOSIAL TERHADAP PENDAPATAN MASYARAKAT SEKITAR HKM SOLOK RADJO DI KECAMATAN LEMBAH GUMANTI - Fitriani, Fahila; Mariya, Sri (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
This study aims to look at community knowledge about Social Forestry and analyze the effect of granting social forestry permits on the income of communities around Community Forests in the Lembah Gumanti District, Solok Regency. With the use of mix methods and the distribution of questionnaires to 45 respondents. Observation data collection techniques and questionnaires to measure community knowledge on a guttman scale as well as descriptive analysis after validity and reliability tests, comparing people's income before and after social forestry using the Paired Sample T Test. The results showed that the level of public knowledge was still lacking regarding social forestry, namely 44.8% while respondents had a good knowledge level of only 17.8% and respondents had sufficient knowledge and 37.8% of respondents. The results showed that the social forestry program was proven to have an impact on the income of the community around HKm Solok Radjo with an increase in income after this social forestry and from the results of the Paired Sample T Test test had a t-count > t-table, so that H0 was rejected and Ha was accepted, namely 5,117> 2,015.